A novel objective method for assessing high‐contrast spatial resolution in CT based on the Rayleigh criterion. Issue 2 (4th February 2017) - Zhang, Pu; Wan, Guoqing; Li, Fei; Li, Xingdong; Liu, Wenli; Wang, Guangzhi
Abstract : Purpose: In China, most quality assessments (QAs) of the high‐contrast resolution of medical computed tomography (CT) equipment is performed by subjective evaluation, which is simple but dependent on observer expertise. The purpose of this study was to compare the accuracy and degree of dispersion of evaluation results from observers with different expertise and to develop an objective, easily understandable new approach to minimize the error caused by the subjective nature of observer evaluation. The accuracy and reproducibility of this new approach was validated and compared using both subjective and objective evaluation methods. Methods: This new objective evaluation method of high‐contrast resolution was based on measurements of CT phantom images. The intensity profile of the aluminum line pairs' (LPs') images was extracted and quantified following the Rayleigh criterion. The interpolation method was employed to improve the consistency of the middle profile lines of each LP group for application of the Rayleigh criterion. With the introduction of a normalized margin, the accuracy of the results increased to the decimal level. Five junior observers and three QA professionals evaluated the high‐contrast resolution of three different CT scanners using the subjective method, modulation transfer function (MTF) method, and the new objective method, and the results were compared statistically. Results: The experimental standard deviations ranged from 0.4 LP/cm to 0.55 LP/cm for subjective visual inspection. The uncertainty of the expert group's results was much lower than that of the volunteer group. The experimental standard deviations of the MTF evaluation, according to both the standard deviation (SD) and point spread function (PSF) methods, were within the intervals of (0.04–0.06) LP/cm and (0.08–0.16) LP/cm, whereas that of the proposed objective evaluation method was approximately 0.02 LP/cm. The experimental data indicated that the results of the new objective evaluation were in accordance with those of the expert group's subjective evaluation and the MTF evaluation. Conclusions: In this study, the subjective evaluation results from experienced observers showed relatively less uncertainty and more accuracy than those from inexperienced observers. Furthermore, a new objective evaluation approach that is easily understood, accurate, and reproducible was developed in this study. Results acquired using this new method were comparable with those of expert groups' subjective evaluation and MTF evaluation. Specialized QA software that integrates the steps implemented in the new method is being developed to enhance the convenience of the approach and assist observers in obtaining accurate and replicable assessment results.